The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1143/jjap.46.l1132
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Magnesium Oxide Sputtering Yields by He and Ar Ions with a Low-Energy Mass-Selected Ion Beam System

Abstract: We consider QCD corrections to Higgs boson production through gluon-gluon fusion in hadron collisions. Using the recently evaluated [14] two-loop amplitude for this process and the corresponding factorization formulae [15]-[18] describing soft-gluon bremsstrahlung at O(α 2 S ), we compute the soft and virtual contributions to the next-to-next-to-leading order cross section. We also discuss soft-gluon resummation at next-to-next-to-leading logarithmic accuracy. Numerical results for Higgs boson production at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The film mass change on the QCM crystal can be monitored by a QCM controller (ULVAC-CRTM9000). The mass resolution of the QCM system is 2.4×10 −11 g. With this QCM system, we have measured sputtering yields of Au [8] and magnesium oxide (MgO) [9,10] by He, Ne, Ar, Kr, or Xe ion beams and found that the measured sputtering yields agree well with earlier data obtained by other experimental groups.…”
Section: Methodssupporting
confidence: 79%
“…The film mass change on the QCM crystal can be monitored by a QCM controller (ULVAC-CRTM9000). The mass resolution of the QCM system is 2.4×10 −11 g. With this QCM system, we have measured sputtering yields of Au [8] and magnesium oxide (MgO) [9,10] by He, Ne, Ar, Kr, or Xe ion beams and found that the measured sputtering yields agree well with earlier data obtained by other experimental groups.…”
Section: Methodssupporting
confidence: 79%
“…For example, experimentally obtained MgO sputtering yield data for He and Ar ion injections in the energy range below about 500 eV have been presented recently by the authors of this article [2]. Other experimentally measured sputtering yields of MgO by low-energy noble gas ions that we are aware of are only those presented in Refs.…”
Section: Introductionmentioning
confidence: 83%
“…[5] do not agree with published experimental data of Refs. [2][3][4]. No experimentally measured or theoretically estimated MgO sputtering yields by Kr ion bombardment in the low-energy range seem to have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Sputter yields of Mg from MgO by low-energy He and Ar ion beams were measured as a function of ion energy by Hine et al (2007) and fit to the following equations:…”
Section: Ion Sputtering At the Time Of M2mentioning
confidence: 99%